Predicting the Impact of Global Climate Change on the Geographic Distribution of Anemochoric Species in Protected Areas - Larissa Alves-de-Lima; Douglas Fernandes Rodrigues Alves; Diego Vinicius Anjos; Fernando Anco Valdivia; Helena Maura Torezan-Silingardi (Atmosphere)
Protected areas are crucial sanctuaries for biodiversity, strictly prohibiting the direct exploitation of natural resources and helping to maintain viable populations and communities. However, even species within these areas face challenges from climate changes. This study compared the present distribution of five woody species (Aspidosperma tomentosum, Kielmeyera coriacea, Peixotoa tomentosa, Qualea multiflora, and Senna velutina) with their projected distribution (in 2080–2100) in 30 protected Brazilian national parks. Our objectives were to evaluate ecological niche models; determine which bioclimatic variables best explain the geographic distribution of species; assess the current distribution of these species; predict changes under distinct future climatic scenarios; and analyze the potential species richness within Brazilian national parks. We overlayed binarized maps of each species and extracted statistical metrics—mean potential, standard deviation, minimum, and maximum potential—using the ‘extract’ function (raster package, v.3.5-2) in the R platform. The results revealed the dynamic nature of species distribution, each one of them being affected by a specific group of factors. All species exhibited changes in their ecological niche or distribution areas in future projections, be it losing areas (A. tomentosum: 26.27–100%; K. coriacea: 38.39–100%; P. tomentosa: 40.46–96.66%; Q. multiflora: 7.34–100%; Senna velutina: 4.52–99.99%) or gaining areas (Q. multiflora: up to 92.21%, and S. velutina: up to 22.07%). We conclude that the potential species richness within Brazilian national parks will be lower in the future. This information is crucial for biodiversity conservation efforts, offering insights into species habitat dynamics and emphasizing the need for adaptive conservation strategies. This study reinforces the urgency of preserving natural ecosystems to ensure a sustainable future for their flora and fauna.